Problems of Objects Identification in Three-dimensional X-ray Tomography; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Mamyrbaev T. A. Talgat Askarbekovich (2016, 2016)
Title screen